The long and short of mental time travel - self-projection over time-scales large and small - Jonathan W Schooler (Frontiers Research Topics, 2015)
Researchers working in many fields of psychology and neuroscience are interested in the temporal structure of experience, as well as the experience of time, at scales of a few milliseconds up to a few seconds as well as days, months, years, and beyond. This Research Topic supposes that broadly speaking, the field of "time psychology" can be organized by distinguishing between "perceptual" and "conceptual" time-scales. Dealing with conceptual time: "mental time travel," also called mental simulation, self-projection, episodic-semantic memory, prospection/foresight, allows humans (and perhaps other animals) to imagine and plan events and experiences in their personal futures, based in large part on memories of their personal pasts, as well as general knowledge. Moreover, contents of human language and thought are fundamentally organized by a temporal dimension, enmeshed with it so thoroughly that it is usually expressible only through spatial metaphors. But what might such notions have to do with experienced durations of events lasting milliseconds up to a few seconds, during the so-called "present moment" of perception-action cycle time? This Research Topic is organized around the general premise that, by considering how mental time travel might "scale down" to time perception (and vice-versa, no less), progress and integrative synthesis within- and across- scientific domains might be facilitated. Bipolar configurations of future- and past-orientations of the self may be repeated in parallel across conceptual and perceptual time-scales, subsumed by a general "Janus-like" feedforward-feedback system for goal-pursuit. As an example, it is notable that the duality of "prospection" and semantic-episodic memory operating at conceptual time-scales has an analogue in perception-action cycle time, namely the interplay of anticipatory attention and working memory. Authors from all areas of psychology and neuroscience are encouraged to submit articles of any format accepted by the journal (Original Research, Methods, Hypothesis & Theory, Reviews, etc.), which might speak to questions about time and temporal phenomena at long and/or short time-scales.